Thermal design power and vectorized instructions behavior. (30th March 2021) - Guermouche, Amina; Orgerie, Anne‐Cécile
Abstract: Vectorized instructions were introduced to improve the performance of applications. However, they come at the cost of an increase in the power consumption. As a consequence, processors are designed to limit their frequency when such instructions are used in order to respect the thermal design power limit. In this paper, we study and compare the impact of thermal design power and Simple Instruction Multiple Data (SIMD) instructions on performance, power and energy consumption of processors and memory. The study is performed on three different architectures providing different characteristics and four applications with different profiles (including one application with different phases, each phase having a different profile). The study shows that, because of processor frequency, performance and power consumption are strongly related to thermal design power. It also shows that AVX512 has unexpected behavior regarding processor power consumption, while DRAM power consumption is impacted by SIMD instructions because of the generated memory throughput. Finally, this paper tackles the impact of turboboost which shows equivalent to better performance for all the studied cases while not always decreasing energy consumption.